Mucoepidermoid Carcinoma of the Lung: A Case Report and Literature Review - S. Alsidawi; J. C. Morris; K. A. Wikenheiser-Brokamp; S. L. Starnes; N. A. Karim (Case Reports in Oncological Medicine)
Introduction. Mucoepidermoid carcinoma (MEC) of the lung is a rare form of lung cancer that is classified into low grade and high grade based on histological features. Surgical resection is the primary treatment for low-grade MEC with excellent outcomes, while high-grade MEC is a more aggressive form of malignancy. Clinical Case. We report a case of a 46-year-old woman who presented with dyspnea on exertion. Imaging studies revealed a mass involving the right upper lobe bronchus. Bronchoscopy, surgical resection, and pathological examination revealed a low-grade MEC with tumor-free margins. No adjuvant treatment was given. Discussion. Primary pulmonary MEC is a rare type of lung cancer with only few reported cases. This patient illustrates a typical presentation for low-grade MEC wherein surgical resection is considered curative. In contrast, high-grade MEC is a more aggressive malignancy with a poorer outcome. The role of targeted therapy directed against EGFR or a novel CRTC1-MAML2 fusion protein expressed in some high-grade tumors is yet to be determined.